Marketing Strategy Telkom Internet Protocol Televison (IPTV) To Increase Subscribers Number for Area Operation Bandung - Alby, Pradipta Wismaya; Purwanegara, Mustika Sufiati; Desiana, Krisnati (The Indonesian Journal of Business Administration, 2012)
Business transformation transfigured fromvoice communication to multimedia (Voice, Data andVideo) is not inevitable in the current telecommunicationsindustry. Telkom develops IPTV (Internet ProtocolTelevision) as an effort to revitalize the Fixed Wirelinebusiness in the middle of the changing landscape of thetelecommunications industry. This IPTV service utilizesthe existing network of fixed wire telephone network(Fixed Wireline). On this technology, one cable can be usedfor various data transmission services, including voice,data and video. Since the commercialization on the early2012, sales performance has decline 37% on the fistquarter and continue to decline in the next month.Referring to the business issue and challenges of the futuretelecommunications business competition, Telkom seeks todevelop a New Wave Telkom Business through IPTVService in an effort to make it as a new revenue generatorreplacing the Fixed Wireline business that has entered thestage of maturity.Business issue exploration aim to identify strengths,weaknesses, opportunities and challenges that occur inTelkom IPTV services in Bandung city, so that the root ofthe problem can be identified. The steps taken in theprocess are collecting secondary data analysis, analyzingbusiness issue exploratory, market research to potentialcustomers, proposing marketing strategy communicationand implementation of IPTV services by Telkom. Based onthe analysis from root of the problem, Telkom IPTVservice marketing activities which are conducted isconsidered incomprehensive and is not on target, thereforeit is necessary to design a marketing strategy that cananswer the root of the problems which are occurred.Proposed business solution includes the application of theMarketing Mix which emphizes on Integrated MarketingCommunication. With the implementation of businesssolutions, such as increasing awareness to target market,marketing communication emphasize on servicedifferentiation, Utilization of Existing Customer Base andSales Bundling Concept can solve existing businessproblems.Keywords: IPTV, Market Penetration, Integrated MarketingCommunication.